Synthetic and Characterization of Some new Schiff bases Complexes with CoII, NiII, CuII and PdII ions - Mahmoud, Muhanned J; Numan, Ahmad T; Al-Obaidi, Omar B M S (Al-Nahrain Journal of Science, 2013)
A new ligand (H4L) and its complexes with (CoII, NiII, CuII and PdII). This ligand was prepared in two steps, in the first step a solution of terephthaldehyde in methanol reacted under refluxe with 1,2-phenylenediamine to give precursore compound which reacted in the second step with 2,4-dihydroxybenzaldehyde to give the ligand. The complexes were synthesized by direct reaction of the corresponding metal chloride with the ligand. The ligand and complexes were characterized by spectroscopic methods [FT-IR, UV-vis, 1HNMR, HPLC and atomic absorption], chloride contant in addition to conductivity measurement. The stability constant K and Gibbs free energy ∆G were calculated for [[Ni2(H2L)Cl2], [Cu2(H2L)Cl2] complexes using spectrophotometer method. The obtained values indicate that these complexes are stable in their solution. The data of these measurements suggest a distorted tetrahedral geometry for CoII, NiII, and CuII complexes and a square planar for PdII complex. The biological activity for the ligand (H4L), and its complexes [Ni2(H2L)Cl2], [Pd2(H2L)Cl2] were studied.